2022
DOI: 10.1097/hjh.0000000000003084
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension-mediated organ damage in masked hypertension

Abstract: Objectives: Masked hypertension -a blood pressure (BP) phenotype characterized by a clinic BP in the normal range but elevated BP outside the office -is associated with early hypertension-mediated organ damage. This study examined early target organ manifestations of masked hypertension diagnosed by home (HBPM) and ambulatory (ABPM) BP monitoring.Methods: Left ventricular (LV) structure and diastolic function measured by echocardiography, microalbuminuria, and coronary artery calcification were evaluated in 42… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…PWV is a noninvasive surrogate marker of arterial stiffness, which has previously been associated with masked hypertension and cardiovascular events [9,11,26]. The association between masked hypertension and increased CACS has previously been suggested as a trend, but not confirmed as significant [27]. As for the carotid arteries, previous studies have shown an association with increased carotid intima thickness [11], but to the best of our knowledge, no previously published study has shown an association with the presence of carotid artery plaques.…”
Section: Discussionmentioning
confidence: 99%
“…PWV is a noninvasive surrogate marker of arterial stiffness, which has previously been associated with masked hypertension and cardiovascular events [9,11,26]. The association between masked hypertension and increased CACS has previously been suggested as a trend, but not confirmed as significant [27]. As for the carotid arteries, previous studies have shown an association with increased carotid intima thickness [11], but to the best of our knowledge, no previously published study has shown an association with the presence of carotid artery plaques.…”
Section: Discussionmentioning
confidence: 99%
“…Masked hypertension, regardless of method used for diagnosis, is cross-sectionally associated with smoking, diabetes, and history of CVD (168,170,171,179,190). A trend, albeit not significant, has been found towards higher prevalence of coronary artery calcifications (191). Masked hypertension diagnosed using home BP is also associated with older age, higher BMI, higher cholesterol, and increased carotid intima-media thickness (170,171,192); MH diagnosed using ambulatory BP is also associated with younger age, obstructive sleep apnea, left ventricular hypertrophy, chronic kidney disease, and BP-lowering medication (168,170,179,190,193,194).…”
Section: Masked Hypertensionmentioning
confidence: 98%
“…CACS >100 is associated with an increased risk of CVD and is used by several major guidelines to suggest initiation or consideration of initiation of lipidlowering therapy and in some guidelines also acetylsalicylic acid (299). The association between MH and CACS has previously been suggested as a trend but not found to be significant (191).…”
Section: Study IImentioning
confidence: 99%
“…Hypertension may affect blood vessels and other organs over time, resulting in a higher risk of heart attack, stroke, kidney impairment, and other medical disorders [5][6][7].…”
Section: Introductionmentioning
confidence: 99%